Optimum scheduling of power generation using digital computers - Dulog, Salvador H. (1973)
This study is an attempt to coordinate fuel costs and transmission losses using exact information for optimum scheduling of power generation by use of digital computers. An iterative procedure is incorporated with load flow calculations being made for each iteration to solve for the transmission losses and variations in voltage phase angles for each bus. In this study, a load flow solution by Gauss-Seidel iterative method using bus admittances was used. For this, subroutine LODFLO with a 20-bus capacity was prepared. Jacobian matrix is then formed using the new bus voltage phase angles which will then be used in solving for the incremental transmission losses. Taking incremental transmission losses into consideration, new schedule of power generation for each unit is computed. Several constraints with regards to the minimum and maximum operating limits of each unit of all generating stations are also considered in the computation of new power generation for each iteration. In each iteration, the following items are also computed : fuel input to each generation, total fuel input, and incremental fuel costs of each station referred to the swing generator. Iterative process is repeated until the total fuel input to the system is minimum. Suggestions and recommendations are made in the hope that future researchers on this subject may be able to use the results of this study.